Optimalisasi Koneksi Local Area Network (LAN) Menggunakan Metode Fasttrack Pada Routerboard Mikrotik - Dian Novianto; Yohanes Setiawan Japriadi; Lukas Tommy (Jurnal Media Infotama, 2023)
Internet network connection is very important to support the performance of an organization. Latency on the network can make the throughput on the network smaller, this can disrupt business processes that require the internet in an organization. To improve internet performance, we need a method that can reduce latency and increase throughput, one of which is fasttrack. Fasttrack is an option available on router devices from Mikrotik which can be used to speed up internet connections on a local network by doing several bypasses on running connections. In this case, the researcher tested the effectiveness of using a fasttrack connection on a RB951Ui-2ND type mikrotik routerboard as the main device in optimizing internet network connections, by making several settings to speed up internet connections. A model is needed for network system development to direct network development, here researchers use a model, namely PPDIOO whose contents are: Preparation, Planning, Design, Implementation, Operations, and Optimization. Supporting tools are also needed to help develop the system, namely the Unified Modeling Language (UML). The test results show that using Mikrotik fasttrack can reduce latency so that internet connection performance increases by up to 59% compared to using standard configurations. In addition, using a fasttrack connection can also reduce CPU resource usage on the used mikrotik routerboard.